USIA DAN BUDAYA PANTANGMAKANAN MEMPENGARUHI PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS HARI KE 7 - Sidabutar, Sondang (Unusa Press, 2013)
Wound healing is a long time in there covery process because of damage to the skin or skin tissue disintegritas. According to Rustam Mochtar(1998), the injured in the birth canal when not accompanied by infection will heal within6-7days. Based on the results of a survey on BPS Ny. Arifin S. Surabaya, from as many as7 of 10 respondents (70%) found the wound is still wet. The purpose of this study was to determine age and cultural picture of incontinence on postpartum mother's perineal wound healing on the seventh day in the BPS Ny. Arifin S. Surabaya. In this research using descriptive method with the study population was all mothers with post natal on the seventh day stit chesin the perineum which controls BPS Ny. Arifin S. Surabaya period from July to August 2008 as many as 49 people. Sampling of non-probability sampling with a sampling technique is saturated. By using questionnaires and observation sheets as research instruments. Data created frequency tables and cross tabulations and then summed. Based on the results of research on maternal postnatal day 9 to 7, obtained the majority of postnatal mother saged <35 years of the perineal wound healed as many as 24 people (66.66%) and in postpartum mothers who do not abstain from the majority of the perineal wound healed as many as17 people (77.27%). By looking at these result it can be concluded that the perineal wound healing can be influenced byculture age and abstinence from food. Therefore, the provision of good information and right by the health officer of the perineal wound care will affect the success of the perineal wound healing process.